Insights into the mechanisms of serplulimab: a distinctive anti-PD-1 monoclonal antibody, in combination with a TIGIT or LAG3 inhibitor in preclinical tumor immunotherapy studies - Yizhou Zhang; Ruicheng Wei; Ge Song; Xinyi Yang; Mengli Zhang; Wei Liu; Aiying Xiong; Xuehan Zhang; Qianhao Li; Wan-Jen Yang; Chencheng Han; Rui Liu; et al. (mAbs)
With more than 20 anti-PD-1/PD-L1 antibodies currently marketed, anti-PD-1 therapy has become a cornerstone of tumor immunotherapy. These agents, however, exhibit notable disparities in their characteristics and clinical performance. For instance, in the field of small cell lung cancer (SCLC) where the majority of anti-PD-1 antibodies have yielded limited success, serplulimab produced impressive survival improvements and was approved for this indication by China’s National Medical Products Administration. Serplulimab’s marketing authorization application also received a positive opinion from the European Medicines Agency. Nevertheless, the molecular mechanism underpinning serplulimab’s superiority over its competitors remains elusive. We characterized the differences between serplulimab with approved PD-1/PD-L1 inhibitors (pembrolizumab and nivolumab) in terms of their binding features and functions in vitro and anti-tumor activity in vivo. Cellular pathways underlying the efficacy of serplulimab were also investigated. In comparison to competitors, serplulimab robustly induces PD-1 receptor endocytosis while fostering weaker PD-1-CD28 cis interactions. This phenomenon could mitigate the dephosphorylation of CD28 by SHP2, thereby facilitating sustained and robust T cell activation. While serplulimab and pembrolizumab exhibited similar performance in vitro and in vivo studies, serplulimab consistently demonstrated superior tumor killing efficacy compared to pembrolizumab upon co-administration with anti-TIGIT or anti-LAG3 inhibitors. Mechanistically, the serplulimab combination effectively reduces tumor microenvironment Treg cell populations, augments effector and memory T cell populations, and more potently modulates genes associated with diverse facets of the immune system, surpassing the effects of the pembrolizumab combination. In summary, our data underscore serplulimab as a differentiated PD-1 monoclonal antibody with best-in-class therapeutic potential.